Healthy Aging: Comparative Analysis of Local Perception and Diet in Two Health Districts of Côte d’Ivoire and Japan - Bonfoh, B.; Koné, B. V.; Koffi, Y. D.; Miyama, T.; Fujimoto, Y.; Fokou, G.; Zinsstag, J.; Sugimura, R.; Makita, K. (Frontiers in Aging, 2022)
Good health and longevity depend on dynamic interactions between factors. Ageing is globally a big challenge. Knowledge, behaviour and diet as well as consumption of animal source food were related to ageing and emerged as the key factors modulating healthy ageing. The study designed to understand the main healthy ageing factors and to derive mutual learning from it for healthy ageing. Qualitative approach has been applied to explore health-related knowledge, attitudes and diet of elders from Ebetsu (Japan) and Tiassalé (Côte d’Ivoire) health districts. The study shows Japanese elders live longer compared to Côte d’Ivoire. Both groups of elders have social networks that support them, and both offer their gained experience to society. While Japanese elders depend on pension and insurance for income and medical treatments, Ivorians depend mostly on their children and social network in old age. In Ebetsu, older members of the community are concerned about the future burden they pose for the old generation if they develop ill-health, making them more resilient to ageing. In Taabo, elders are considered to being culturally and socially useful to the society. Elders in Ebetsu pointed out that for healthy ageing, education on diet at a younger age, physical activities and access to basic social services are key aspects. This was not observed in Taabo’s context. Being inactive and dependent on others, were described as the most worrying situations for elders in Ebetsu, as it is perceived to increase the risk of non-communicable diseases and anxiety. Elders in Ebetsu have good knowledge on what constitutes a healthy diet to maintain good health. In Côte d’Ivoire, diet is imbalanced and the whole family consumes the same meal made mainly with high energy staples and little protein. The consciousness of ageing is universal, but healthy ageing varies according to the social systems, education, and knowledge on diet transition. Physical activities, protein-energy balance in diet, and social networks are key for healthy ageing in both contexts. The challenge is to find ways to increase knowledge with regards to healthy ageing and to strengthen the support system so that healthy ageing becomes